The Major Plant-derived Cannabinoid Δ9-Tetrahydrocannabinol Promotes Hypertrophy and Macrophage Infiltration in Adipose Tissue - Wong, A.; Gunasekaran, N.; Hancock, D. P.; Denyer, G. S.; Meng, L.; Radford, J. L.; McGregor, I. S.; Arnold, J. C. (Hormone and Metabolic Research, 2012)
Synthetic cannabinoid receptor agonists activate lipoprotein lipase and the formation of lipid droplets in cultured adipocytes. Here we extend this work by examining whether Δ9-tetrahydrocannabinol (THC), a major plant-derived cannabinoid, increases adipocyte size in vivo. Further, possibly as a consequence of hypertrophy, we hypothesize that THC exposure promotes macrophage infiltration into adipose tissue, an inflammatory state observed in obese individuals. Rats repeatedly exposed to THC in vivo had reduced body weight, fat pad weight, and ingested less food over the drug injection period. However, THC promoted adipocyte hypertrophy that was accompanied by a significant increase in cytosolic phosphoenolpyruvate carboxykinase (PEPCK-C) expression, an enzyme important in packaging triglycerides. We also showed that THC induced macrophage infiltration and increased expression of the inflammatory cytokine tumor necrosis factor alpha (TNF-α) in adipose tissue but did not induce apoptosis as measured by TUNEL staining. That THC increased adipocyte cell size in the absence of greater food intake, body weight and fat provides a unique model to explore mechanisms underlying changes in adipocyte size associated with a mild inflammatory state in fat tissue.
Keywords: fat; obesity; cannabis; inflammation; TNF-α